O violão brasileiro e seu ensino: uma visão a partir de uma instituição de ensino superior no Nordeste brasileiro - Gaiao, Lucas Dantas (2024)
This study's primary aim is to understand how different facets of brazilian guitar are integrated into guitar courses at a higher education institution in northeastern Brazil. To this end, a field research study with a qualitative approach based on semi-structured interviews was conducted. Data collected through these interviews were analyzed alongside additional data derived from a literature review and a document analysis of course syllabi and other documents related to guitar instruction at the institution. The theoretical framework was developed by exploring the concepts of Brazilian music and Brazilian guitar, with texts discussing the various facets of the guitar in Brazilian music, reflections on the training of guitarists at the higher education level, and considerations on the challenges and prospects for music education in contemporary higher education. Triangulating data from interviews, literature, and the theoretical foundation, the study revealed distinct manifestations of Brazilian guitar, connected to its multiple roles and repertoires, leading to a discussion on how these diverse guitar styles appear in higher education, especially in this institution. Interview responses indicated varying conceptions of the guitar and its relationship with Brazilian music, as well as different understandings regarding the teaching of the instrument at the tertiary level. Based on the findings from these analyses, we identify opportunities for constructing a Brazilian approach to guitar teaching, where national repertoire is approached through a uniquely Brazilian teaching perspective, avoiding uncritical imports and the misconception that merely changing the repertoire equates to a paradigm shift. Moreover, this study highlights the need for further research on: Brazilian guitar as a cultural and musical phenomenon, its diverse roles within Brazilian music, and the implications of a broadened, pluralistic understanding of this instrument in academic settings. This expanded perspective aims to foster greater incorporation of Brazilian repertoire, practices, and knowledge within the academic environment.